Ð Ð¾Ð»ÑŒ Ñ„Ð°Ð· ÐºÐ»ÐµÑ‚Ð¾Ñ‡Ð½Ð¾Ð³Ð¾ Ñ†Ð¸ÐºÐ»Ð° Ð¸ Ð¼Ð¾Ñ€Ñ„Ð¾Ð»Ð¾Ð³Ð¸Ð¸ Ð¿Ñ€Ð¾Ð½ÑƒÐºÐ»ÐµÑƒÑÐ¾Ð² Ð² Ð¶Ð¸Ð·Ð½ÐµÑÐ¿Ð¾ÑÐ¾Ð±Ð½Ð¾ÑÑ‚Ð¸ Ð½Ð°Ñ‚Ð¸Ð²Ð½Ñ‹Ñ… Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð·Ð¸Ð³Ð¾Ñ‚ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Petrushko, M. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2005)
The cryopreservation results of human embryos being at zygote stage are presented. There was studied the effect of pronuclei morphology on zygote survival after freeze-thawing. The role of cell cycle phases in the zygote cryopreservation efficiency was found.